IMPLEMENTASI ADIWIYATA DALAM MENANAMKAN KARAKTER PEDULI LINGKUNGAN KELAS III DI SD NEGERI BHAYANGKARI KOTA SERANG - Akbarul Fitra; Jerry Rahman Hakim; Ana Nurhasanah (STKIP Persada Khatulistiwa Sintang, 2023)
This research is aims to describe the Implementation of Adiwiyata in Planting Environmental Care Grade 3 at SDN Bhayangkari, Serang City. This research uses descriptive qualitative methods to build knowledge through understanding by investigating a social phenomenon. Objectives there are 2 Knowing the process of implementing Adiwiyata and the Impact of Adiwiyata Implementation. The results of the study include: first, the process of implementing adiwiyata at Bhayangkari State Elementary School in Serang City, namely, habituation activities, understanding in learning and extracurricular activities. Second, the impact on students from the implementation of adiwiyata, has positive results and has a good influence on the character of caring for the student's environment, namely that there has been a change in students in the role of maintaining the environment and compliance with regulations.